Sharing Experiences and Seeking Informal Justice Online: A Grounded Theory Analysis of Zoombombing Victimization on Reddit - Lee, Claire Seungeun (Victims & offenders, 2023)
During the COVID-19 pandemic, Zoombombing emerged as a new form of online disruption/harassment characterized by unintended and unsolicited virtual visits by both strangers and known individuals via Zoom. The current study utilizes a grounded theory-based qualitative analysis of over 1,000 posts on Reddit to explore discussions around Zoombombing victimization incidents. This paper reveals how Zoombombing victimization subreddits function as communities for sharing victimization stories, user perceptions, and support while further developing a space that promotes informal justice online. The implications include an enhanced understanding of how Zoombombing occurs and the role of online forums and cyberpolicing tools in preventing and discussing victimization.